Human remains in Slovenian museums and memorial sites - Ramšak, Mojca (Monitor ISH, 2023)
The article deals with different types of human remains exhibited in Slovenian museums or memorials, educational institutions and other places in Slovenia. It presents the typology of human remains, the legal framework and the ethical guidelines for their respectful handling. At the same time, the author points out that Slovenia has no challenges with repatriation requests, as historically it was not a dominant colonial power that would accumulate its collections in this way.
Keywords: človeški ostanki; ethics; etika; human remains; material culture; materialna kultura; museum; muzej; Slovenia; Slovenija